Rational pharmaceutical management of medical oxygen in community-acquired pneumonia - M. Ya. Sekh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Medical oxygen has been currently considered as a medication according to the Ukrainian and worldwide data. The WHO has included it into the list of the main medical agents. Moreover, medical oxygen has a broad application spectrum and here it may be the only remedy that cannot be replaced by the analogous one. The most common symptoms of respiratory problems are oxygenation disorder and hypoxemia which require the application of medical oxygen. This factor determined the target group of our research, namely, the patients with community-acquired pneumonia of moderate and severe course. The aim of the research was to study the state and expense of oxygen provision for patients with community-acquired pneumonia who were admitted to the internal unit of one of the health care institutions in Lviv. Medical documentation was the object of the research. It included: reporting/control documentation and medical prescriptions of patients diagnosed with community-acquired pneumonia. The study involved the application of systemic analysis, as well as analytical and comparative, information and search, clinical and economic, bibliographic of research methods. The paper describes the importance of oxygen therapy for hypoxia treatment in certain pathological conditions, in particular community-acquired pneumonia. We performed an analysis of the state and expense of oxygen provision in the Lviv Regional Clinical Hospital as well as the patients with community-acquired pneumonia. The study was carried out in two periods (2006 and 2017). It has been established that the total expenses associated with oxygen were increased by 10 times in the hryvnia and by 2 times in dollar equivalents for 11 years. In addition, from the cost of all medicines purchased by the hospital during 2017, 8% was spent on medical oxygen. In the course of our study, the need for oxygen for a single therapeutic patient with non-hospital pneumonia is about 25 m3. The total cost of providing them with this category of patients has also grown almost 10 times in hryvnia and 2 times in dollar equivalents - from 41.56 UAH (8.23 $)/patient) to 477.72 UAH (17.63 $)/patient in 2006 and 2017, respectively. This certainly leads to a significant increase in the costly pharmacotherapy of patients with community-acquired pneumonia. Вeside this, the analysis has revealed a list of problems associated with outdated material and technical equipment, weariness of equipment, danger of explosion, and continuously growing expense of medical oxygen which forces the search for new and safer patient provision methods. Medical oxygen becomes a financial burden in clinical practice particularly under conditions of restricted financing in the branch of health care. Herein, it remains the main and compulsory component of pathogenic therapy in community-acquired pneumonia. The abovementioned problematic aspects require the urgent solution that, in our opinion, can be reached with the application of rational pharmaceutical management.